Degradation of trichloroethene by citric acid chelated Fe(II) catalyzing sodium percarbonate in the environment of sodium dodecyl sulfate aqueous solution. (October 2021) - Huang, Jingyao; Zhou, Zhengyuan; Ali, Meesam; Gu, Xiaogang; Danish, Muhammad; Sui, Qian; Lyu, Shuguang
Abstract: In this study, the common chlorinated solvent trichloroethene (TCE) was selected as the target contaminant. The aqueous solution after solubilization treatment (containing TCE and sodium dodecyl sulfate (SDS)) was used as the research object to carry out the remediation technology research of citric acid (CA) enhanced Fe(II) activation in sodium percarbonate (SPC) system. In 0.15 mM TCE and 1 critical micelle concentration (CMC) SDS solution, CA chelating Fe(II) activated SPC could effectively promote 93.2% degradation of TCE when the dosages of SPC, Fe(II) and CA were 3.0, 6.0 and 3.0 mM, respectively. SDS had a significant inhibitory effect on the degradation of TCE, and the surface tension changed after the reaction. The addition of CA greatly increased the generation of hydroxyl radicals (HO) in the system, while the removal of TCE was mainly attributed to HO, and the removed TCE was almost completely dechlorinated. The pH range from 3 to 7 could keep the TCE degradation above 80.0%. In the actual groundwater remediation, this technique could also efficiently degrade TCE (including SDS), showing a great application potential and development prospective in practice. Graphical abstract: Image 1 Highlights: CA promoted the production of HO in the SPC/Fe(II) system. SDS changed the surface tension in the aqueous solution before and after the Fenton reaction. The addition of CA expanded the application range of pH for advanced oxidation process. The SPC/Fe(II)/CA process can be well applied in the actual groundwater remediation.